Ebola Virus in West Africa as National Security Threat to the United States of America - Zulfikar, Kemas Muhammad (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2020)
This study sought to explain the reasons the United States (US) makes the Ebola virus became pandemic in West Africa as a priority of US national security. This research is shows that the US lowered its troops to 3,000 troops to Liberia. In addition, countries in the West African region in particular Guinea, Sierra Leone and Liberia as countries affected by the Ebola geopolitically located in the Sahel region highly vulnerable to conflict likely to be used by terrorist groups. Through linkages framework of national security and foreign policy, this study will explain the reasons behind the US decision in making the Ebola virus as a national security priority. By using literature and data analysis, this research concluded that the US has Ebola as a national security priority for the United States wants to prevent the use of Ebola virus for bioterrorism events. This is confirmed by the adoption of the US strategy of selective engagement through the use of the countries in West Africa as an instrument for anticipating such bioterrorism.